Rapid Assessment of Insect Steroid Hormone Entry Into Cultured Cells - Masterson, Mitchell; Bittar, Riyan; Chu, Hannah; Yamanaka, Naoki; Haga-Yamanaka, Sachiko (Frontiers in Physiology, 2022)
Steroid hormones control development and homeostasis in a wide variety of animals by interacting with intracellular nuclear receptors. Recent discoveries in the fruit fly Drosophila melanogaster revealed that insect steroid hormones or ecdysteroids are incorporated into cells through a membrane transporter named Ecdysone Importer (EcI), which may become a novel target for manipulating steroid hormone signaling in insects. In this study, we established an assay system that can rapidly assess EcI-mediated ecdysteroid entry into cultured cells. Using NanoLuc Binary Technology, we first developed an assay to detect ligand-dependent heterodimerization of the ecdysone receptor (EcR) and retinoid X receptor (RXR) in human embryonic kidney (HEK) 293T cells. We also developed HEK293 cells that stably express EcI. By combining these tools, we can monitor ecdysteroid entry into the cells in real time, making it an ideal system to assess EcI-mediated steroid hormone incorporation into animal cells.